2023
DOI: 10.1002/smll.202300900
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Catalysis in Size and Volume Dual‐Confined Space of Integrated Nanochannel‐Electrodes Chip for Enhanced Impedance Detection of Salmonella

Abstract: Nanochannel‐based confinement effect is a fascinating signal transduction strategy for high‐performance sensing, but only size confinement is focused on while other confinement effects are unexplored. Here, a highly integrated nanochannel‐electrodes chip (INEC) is created and a size/volume‐dual‐confinement enzyme catalysis model for rapid and sensitive bacteria detection is developed. The INEC, by directly sandwiching a nanochannel chip (60 µm in thickness) in nanoporous gold layers, creates a micro‐droplet‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“… This indicated that the enzymatic reaction kinetics of TYR was higher in our present confined environment, suggesting that a suitable confinement could enhance enzyme activity. Reasonably, this finding could be ascribed to the strengthened molecular collision between the substrate and enzyme. , In addition, the observed K m value was lower than that previously identified in the process of catechol catalytic oxidization as catechol was usually regarded as the most suitable substrate for TYR. Therefore, in a restricted nanospace, TYR exhibited a much higher affinity for Tyr, implying that Tyr may be the most suitable substrate for TYR in this given scenario.…”
Section: Resultsmentioning
confidence: 99%
“… This indicated that the enzymatic reaction kinetics of TYR was higher in our present confined environment, suggesting that a suitable confinement could enhance enzyme activity. Reasonably, this finding could be ascribed to the strengthened molecular collision between the substrate and enzyme. , In addition, the observed K m value was lower than that previously identified in the process of catechol catalytic oxidization as catechol was usually regarded as the most suitable substrate for TYR. Therefore, in a restricted nanospace, TYR exhibited a much higher affinity for Tyr, implying that Tyr may be the most suitable substrate for TYR in this given scenario.…”
Section: Resultsmentioning
confidence: 99%